Transformasi Pelayanan KSPPS BMT MitraMu Jepara dengan Aplikasi MitraMu Mobile - Nur Arif Mustofa; Miswan Ansori (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study discusses the transformation of KSPPS BMT MitraMu Jepara services through the implementation of the MitraMu Mobile application. The main objective of this study is to evaluate how innovation and implementation of this application affect the improvement of services to BMT MitraMu members. This study uses a qualitative approach with a descriptive method, where data is obtained through interviews with BMT and several members who use the application. The results of the study indicate that the implementation of the MitraMu Mobile application has significantly increased accessibility, service efficiency, and member satisfaction. Members can make financial transactions anytime and anywhere, which drastically reduces the need to visit the physical BMT office. This application is also equipped with an adequate security system, thus increasing the sense of security and comfort of members in making transactions. In conclusion, digital transformation through the MitraMu Mobile application has proven effective in improving the quality of service at BMT MitraMu Jepara, despite challenges in technology adaptation by members.